2021
DOI: 10.1042/bsr20212026
|View full text |Cite
|
Sign up to set email alerts
|

ZNF76 predicts prognosis and response to platinum chemotherapy in human ovarian cancer

Abstract: Ovarian cancer (OV) is the most lethal gynecologic malignancy. One major reason of the high mortality of the disease is due to platinum-based chemotherapy resistance. Increasing evidence reveals the important biological functions and clinical significance of zinc finger proteins (ZNFs) in OV. In this study, the relationship between zinc finger protein 76 (ZNF76) and clinical outcome and platinum resistance in patients with OV was explored. We further analyzed ZNF76 expression via multiple gene expression datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…We validated the differential expression of ZNF76-RI events between patients' CRC tissues and paracancerous tissues by RT-PCR, and the results were consistent with our bioinformatics analysis. Furthermore, consistent with our ndings, Tian et al also believe that ZNF76 may serve as a promising prognostic-related biomarker in cancer [35]. Our ndings suggest that alternative spliceosomes of ZNF76 and other ZNFs may play a potentially important role in the development of CRC.…”
Section: Discussionsupporting
confidence: 91%
“…We validated the differential expression of ZNF76-RI events between patients' CRC tissues and paracancerous tissues by RT-PCR, and the results were consistent with our bioinformatics analysis. Furthermore, consistent with our ndings, Tian et al also believe that ZNF76 may serve as a promising prognostic-related biomarker in cancer [35]. Our ndings suggest that alternative spliceosomes of ZNF76 and other ZNFs may play a potentially important role in the development of CRC.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that LSM2 plays a role in the disease progression of lung cancer [ 30 ]. Hua et al also found that LSM2 may be associated with the prognosis of ovarian cancer and may be involved in influencing the response to treatment with platinum-based drugs [ 31 ]. Abnormal expression of LSM4 is closely related to the occurrence and development of a variety of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…14 Additionally, it has also been shown that PFDN6 expression is significantly associated with the prognosis of patients with ovarian cancer. 15 However, studies investigating the role of PFDN6 in CRC are limited. Therefore, an in-depth investigation of CRC will provide new insights into its clinical diagnosis and treatment.…”
Section: What This Study Addsmentioning
confidence: 99%